2014
DOI: 10.1016/j.joca.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The influence of experimental anterior knee pain during running on electromyography and articular cartilage metabolism

Abstract: During a 30-min run, AKP acutely alters midstance VM, VL, and GA EMG amplitude. AKP during a 30-min run does not, however, acutely influence articular cartilage metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
1
11
2
Order By: Relevance
“…Fitting with previous research [15,17,19], the present results show that physical activity intensity influences the magnitude of serum COMP increase. The present results also indicate that serum COMP concentration returned to baseline no later than 30 min after ambulating 4000 steps, independent of ambulation speed.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Fitting with previous research [15,17,19], the present results show that physical activity intensity influences the magnitude of serum COMP increase. The present results also indicate that serum COMP concentration returned to baseline no later than 30 min after ambulating 4000 steps, independent of ambulation speed.…”
Section: Discussionsupporting
confidence: 89%
“…In healthy subjects, previous serum COMP [18] and MRI data [28] suggest that increased serum COMP concentration reflects acute cartilage breakdown due to repetitive loads associated with ambulation. Also, increased serum COMP concentration is thought to indicate normal cartilage turnover [15,17,19]. Because our subjects were healthy and young, and the exercise interventions were low demand and of a short duration, we assume that the observed serum COMP increases represent normal cartilage metabolism.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Results demonstrated a significant increase in serum COMP, which remained elevated for 2 h post, but had returned to baseline within 24 h. Prolonged bouts of acute running, i.e., following running a marathon has been associated with a 24–60% (Neidhart et al 2000; Kim et al 2009), increase in COMP. In healthy individuals, 30 min of running exercise has been associated with a 16–36% increase in COMP (Denning et al 2014; Firner et al 2018). Thus, COMP appears to respond in a ‘dose dependent’ fashion to acute exercise bouts (Neidhart et al 2000; Mündermann et al 2005; Kersting et al 2005; Kim et al 2009; Niehoff et al 2010).…”
Section: Acute Serum Biomarker Response To Joint Loadingmentioning
confidence: 99%
“…However, the increase in VM EMG activation during the stair ascent task performed after the loading protocol did not correlate with the increase in pain. Denning et al [ 48 ] have found that experimentally-induced knee pain during running actually decreased VM and VL EMG amplitude. As such, pain itself might not be responsible for the increase in VM EMG amplitude found in the present study.…”
Section: Discussionmentioning
confidence: 99%